2020
DOI: 10.37828/em.2020.37.6
|View full text |Cite
|
Sign up to set email alerts
|

Paeonia caucasica (Schipcz.) Schipcz. in phytocenoses of the Republic of Adygea

Abstract: Populations of Paeonia caucasica (Schipcz.) Schipcz., 1937 growing in various forest phytocenoses were discovered and studied during the monitoring of protected plant species in the Republic of Adygea. The allocation of the species to a certain range of altitudes above sea level and types of communities were defined. The ontogenetic structure and states of plants were identified, and the state of P. caucasica populations was assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Additionally, it was reported that 30 mg/L ABA had a significant inhibitory effect on the seed germination of herbaceous peony hybrid 'Fen Yu Nu' × 'Fen Yu Lou' [85]. The activities of ABA and GA 3 in the seeds of various peonies were shown to be dependent on given environmental factors [60,64]; winter or low temperatures led to the accumulation of ABA in seeds, which induced dormancy, whereas spring or warm temperatures led to ABA degradation and the accumulation of GA 3 , which triggered dormancy release and germination [44,72,86]. In herbaceous peonies, the following optimal concentrations of GA 3 for radicle emergence were reported: 250 mg L −1 for P. corsica [42] and 300 mg L −1 for P. lactiflora [76].…”
Section: Hormones Enzymes and Genesmentioning
confidence: 99%
“…Additionally, it was reported that 30 mg/L ABA had a significant inhibitory effect on the seed germination of herbaceous peony hybrid 'Fen Yu Nu' × 'Fen Yu Lou' [85]. The activities of ABA and GA 3 in the seeds of various peonies were shown to be dependent on given environmental factors [60,64]; winter or low temperatures led to the accumulation of ABA in seeds, which induced dormancy, whereas spring or warm temperatures led to ABA degradation and the accumulation of GA 3 , which triggered dormancy release and germination [44,72,86]. In herbaceous peonies, the following optimal concentrations of GA 3 for radicle emergence were reported: 250 mg L −1 for P. corsica [42] and 300 mg L −1 for P. lactiflora [76].…”
Section: Hormones Enzymes and Genesmentioning
confidence: 99%